Characteristics of Density Distribution and Densification on Medium and Small Indonesian Municipalities - Aria Leo Bimantara; Muhammad Sani Roychansyah; Keiichi Ogawa (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2022)
While many studies on urban compactness measured built-up area (intensity), this study explored population density in forms of gradients. Also, medium and small cities (in this case, municipalities due to having autonomous economies), through inquiring their characteristics in common, could provide early insights for anticipating further growths. Density database was made, combined with cadastral data. Two kinds of urban growth pattern (i.e. concentric and linear) were comprehended to extract gradient patterns from the cities using three indices. Through assigning a time span (2010–2018), the densification rates were also derived. The results indicate that there was a transformation from linear to concentric pattern while populations increased, yet not rare to total sprawling. Besides, there were influences on the compactness states from how the cities are positioned among the others within their local clusters where, on one hand, being too close to large cities would promote sprawling in long term while, on the other hand, being surrounded evenly by other cities is likely advantageous. Nevertheless, the degree of these advantages was not prevailing fairly across the Indonesian regions. Given the complexity and multidisciplinary nature of urban form, these findings are considerable for further planning and studies.